Legal Framework for Managing Private Archival Materials: Current Status and Proposed Solutions - Tran, Thi Hoan; Bui, Ngoc Tuan (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The management of archival documents in general, and private archival documents in particular, plays a crucial role in implementing policy regimes, contributing to the preservation, maintenance, and utilization of the archival value of individuals, organizations, and even national treasures. However, in the current context, the institutional framework for managing private archival documents remains incomplete, and the human and financial resources allocated to this task are limited. Issues regarding rights of donation, ownership, and usage rights of archival documents still present numerous gaps in both practice and legality. This article discusses the necessity of managing private archival documents, the current situation, and several solutions to improve legal frameworks for managing private archival documents amidst amendments to the Archives Law of 2011.